PROFIL KARAKTER TANAMAN PADI POPULASI BULK GENERASI F4 PADA KONDISI KAHAT HARA NPK - Muhammad Hatta; Rosmayati Rosmayati (Jurnal Floratek, 2015)
High dependence of rice farming on chemical fertilizers has an adverse impact on environment and the economy. Thus, it is necessary to develop varieties that are tolerant to low nutrient conditions. This experiment was arranged in a randomized block design with a total sample of 88 plants. The results showed that grain weight per panicle was the variable that has the highest diversity, followed by the number of leaf chlorosis per productive tillers and number of panicles. Plant height was a variable that has the lowest diversity. Moreover, the number of panicles showed significant positive skewness, which indicates that the number of panicles have complementary gene interaction. Plant height, number of leaf chlorosis per productive tiller, and number of panicles had positive kurtosis values, which indicate that these variables are controlled by a few genes. In contrast, grain weight per panicle, number of tillers, and the number of leaves had negative kurtosis values, which indicate that these variables are controlled by many genes. F4 bulk population gave 32 clusters, which indicate that this F4 population has a high variation among individuals.